Synthesis and excited state spectroscopy of tris (distyrylbenzenyl)amine-cored electroluminescent dendrimers - Palsson, L.-O.; Beavington, R.; Frampton, M.J.; Lupton, J.M.; Magennis, S.W.; Markham, J.P.J.; Pillow, J.N.G.; Burn, P.L.; Samuel, I.D.W. (Macromolecules, 2002)
An efficient strategy has been developed for the preparation of four generations of electroluminescent dendrimers that contain tris(distyrylbenzenyl)amine cores, stilbene dendrons, and tert-butyl surface groups. The synthesis involved coupling of benzylphosphonate focused dendrons with tris(4'-formylstilbenyl)amine to give the dendrimers in yields ranging from 63 to 86%. The dendrimers were found to be monodisperse by gel-permeation chromatography. The zeroeth generation dendrimer underwent two chemically reversible oxidations while for the higher generations only one chemically reversible oxidation was observed. On reduction, the dendrimers were found to aggregate with the level of aggregation dependent on the switching potential. The four dendrimer generations were investigated by means of optical spectroscopy. Time-resolved luminescence of the dendrimers in solution showed that the excited state of each of the generations had a monoexponential decay with a lifetime of 1.8 ns. The photoluminescence quantum yield (PLQY) of the dendrimers in solution was independent of generation and was found to be in the region of 0.62. This suggests that the origin of the luminescence is the same for all dendrimer generations. In thin films, time-resolved luminescence of the zeroeth dendrimer generation revealed a long-lived luminescence component in the red part of the spectrum with a lifetime of 7.5 ns. This emission component could not be found in the first, second, and third generation dendrimers, where the long-lived luminescence had a lifetime of 1.5-3 ns at all detection wavelengths. Furthermore, the PLQY of the dendrimer films was found to be dependent on generation and significantly lower than the solution PLQYs. The dendrimer film PLQY increased with generation from 5% for the zereoth generation to 12% for the third generation. The differences observed in the time-resolved luminescence and PLQY of the dendrimers in the solid state arise from the fact that intermolecular interactions between the emissive cores of the dendrimers are considerably stronger in the zeroeth generation than in higher generations. The intermolecular interactions result in an aggregate, which we ascribe to an excited-state species, such as an excimer.
EPrint Processing Status: Publisher does not permit full text to be deposited
Keywords: Light-emitting-diodes; Conjugated polymers; Phenylacetylene dendrimers; Stilbenoid dendrimers; Organic dendrimer; Charge-transport; Fluorescence; Excitations; Photoluminescence; Generation.